Hydrogenation of N-Benzylideneaniline by Palladium (Ii) Catalysts with Phosphorus-Nitrogen Ligands Using Formic Acid as a Renewable Hydrogen Source - Moya-Duran, S; Moya-Duran, S; Perez-Zuniga, C; Perez-Zuniga, C (Elsevier B.V., 2019)
This paper reports the hydrogenation of N-benzylideneaniline catalysed by Pd(II) compounds containing heterobidentated phosphorus-nitrogen (PN) ligands. The general formulas of the catalysts are cis-[PdCl2(L1)] and [PdCl(PPh3)(L1)]Cl (where L1= Ph2PCH2py, Ph2PNCH3py, Ph2PNHpy, Ph2PNHpym and Ph2Pqn). The hydrogenation of N-benzylideneaniline was carried out using propan-2-ol or formic acid as the hydrogen source. The catalytic activity was studied under different conditions by varying the base (NaOH and tert-butoxide) and the base/catalyst ratio (B/C = 20/1 and 50/1.Additionally, triethylamine was also used with a base/catalyst ratio of B/C = 500/1. It was found that palladium catalysts containing hemilabile heterobidentated ligands showed high catalytic activity and selectivity for the hydrogenation of N-benzylideneaniline. The catalysts cis-[PdCl2(Ph2PNHPy)] (2) and [PdCl(Ph2Pqn)(PPh3)]Cl (6) maintained the activities when the reactor was recharged with a fresh substrate (1000/1 substrate/catalyst ratio). It was also found that catalytic hydrogenation works well with only formic acid, with its activities ranging close to 100% for the 2 and 6 complexes. © 2018